Accurate Interpretation of SARS-CoV-2 Antigen Detection by Immunochromatography - Shao, Wenxia (Frontiers in Medicine, 2022)
SARS-CoV-2 is a serious infectious respiratory virus that can cause lung, heart, kidney, and liver damage and even cause death. Early diagnosis of SARS-CoV-2 infection is vital for epidemic prevention and control. At present, the gold standard of COVID-19 diagnosis is nucleic acid detection of SARS-CoV-2. However, the nucleic acid detection of SARS-CoV-2 requires high site requirements and technology requirements, and the detection is time-consuming and cannot fully meet clinical needs. Although SARS-CoV-2 antigen test results cannot be directly used to diagnose COVID-19, positive results can be used for the early triage and rapid management of suspected populations. However, due to the limitations of the methodology itself, the SARS-CoV-2 antigen test is prone to produce false-positive and false-negative results in the process of detection. It is urgent to develop a batch of SARS-CoV-2 antigen reagents based on new detection technology and detection principles to overcome the defects of existing technologies.